Voter participation factors in the South African Local Government Elections: influences and propositions for voter education - Mehlape, M. M. (Journal of Public Administration and Development Alternatives (JPADA), 2016)
Legitimate democracy relies on the widespread public participation in the election process. Voter participation is dependent on voter registration. Voters should indicate from a very early date determined by government their intention to participate in the voting process through a legitimate registration. The article reports findings of a study that investigated factors influencing voter participation in the registration towards the 2016 South African Local Government Elections in South Africa using the case of Mankweng community. The article argues that there is a need for voter education in South Africa before the actual election process take place. This is to increase a unified perception about the value of voter participation on democracy performance. The study applied a mixed method approach in which a sequential exploratory strategy was applied to data collection and analysis. The Mankweng Township within the Polokwane Local Municipality serves as a unit of analysis. Findings of the study revealed mixed perceptions amongst the variety of participants view on participation in the 2016 elections. This has indicated dichotomies amongst age groups and social statuses, about voting and participation significance in the current democratic dispensation in South Africa.
Journal article
Keywords: Democracy; Democratic dispensation; Voter registration; Local government elections; Voter education; Elections -- South Africa; Voter registration -- South Africa; Democracy -- South Africa